2017
DOI: 10.1055/s-0043-120764
|View full text |Cite|
|
Sign up to set email alerts
|

Radiological Diagnoses in the Context of Emigration: Infectious diseases

Abstract: Background Globalization and emigration impact on the spectrum of diseases challenging health care systems. Medical practitioners have to particularly prepare for infectious diseases. Methods The database of a health care center specialized on tropical medicine was screened for patients with history of migration and one of the following diagnoses: Cystic echinococcosis, tuberculosis, schistosomiasis, visceral leishmaniosis, and neurocysticercosis. Representative casuistics were prepared from select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…We described the clinical, laboratory and radiological features of 10 cases with VL, which is sporadic in our region. Generally, there is a long duration from symptom onset until the diagnosis of VL like in our series (6,14,15). We found that the mean duration between symptom onset and diagnosis was long, with over 60 days.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…We described the clinical, laboratory and radiological features of 10 cases with VL, which is sporadic in our region. Generally, there is a long duration from symptom onset until the diagnosis of VL like in our series (6,14,15). We found that the mean duration between symptom onset and diagnosis was long, with over 60 days.…”
Section: Discussionsupporting
confidence: 61%
“…The diagnosis of VL can be frequently difficult due to the long incubation period and non-specific symptoms (1,7). In sporadic regions, VL is not number one in the differential diagnosis list and specific diagnostic tests, such as detection of amastigotes in BM smears and serological tests may not be positive in the early period of the disease (6,7). Although the serological tests were positive in all patients presented here, there was a delay…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations